Pengembangan pembelajaran PAI model student facilitator and explaining pada kelas VII SMP Negeri 1 Puri Mojokerto - Hariris Nurcahyo (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
Learning PAI (Islamic Education) seeks to increase the interest of students to develop the knowledge, skills and ability to think about nature and its contents are full of secrets endless. Based Permendiknas No. 23 of 2006, Standard Competency Education Unit (SKL-SP) SMP / MTS include: students can find and apply information from the environment and other sources logically, critically and creatively, and students can demonstrate the ability analyze and solve problems in everyday life. The purpose of development research are: 1) to describe the model of PAI that has been applied in SMP Negeri 1 Puri Mojokerto 2) Describe the product feasibility PAI learning for junior secondary students and secondary review of aspects of the model Student Facilitator and Explaining 3) Produce Learning PAI student Facilitator and explaining the model that corresponds to the culture and character of students in SMP Negeri 1 Puri Mojokerto Products PAI learning facilitator and explaining the model student has been accomplished based analysis of trial data. Based on the measures that have been implemented can be concluded as follows. 1). Products are revised based on theoretically and empirically test results are: Revised by students by questionnaire: Change to increase the attractiveness of the model 2) Products that are developed interesting for classical learning in the classroom and independently. 3) The product of these products can ease the burden of teachers in teaching. 4) The results of expert validation and testing, PAI Learning Facilitator and explaining the model student is fit for use for subjects of Natural Sciences (PAI). 5) Products that are developed can increase students' motivation, and motivation is one of the conditions of implementation of productive models.